Thermal annealing behavior of hydrogen and surface topography of H2+ ion implanted tungsten. Issue 7 (3rd July 2018) - Zhang, Jiandong; Jiang, Weilin; Zhu, Zihua; Shao, Lin; Price, Lloyd; Zhao, Jiangtao; Wang, Tieshan
ABSTRACT: Tungsten (W) has been proposed as a plasma-facing material in fusion reactors due to its outstanding properties. Degradation of the material properties is expected to occur as a result of hydrogen (H) isotope permeation and trapping in W. In this study, two polycrystalline W plates were implanted with 80 keV H2 + ions to a fluence of 2 × 10 21 H + /m 2 at room temperature (RT). Time-of-flight secondary ion mass spectrometry (ToF-SIMS), focused ion beam (FIB), and scanning electron microscopy (SEM) were used for sample characterization. The SIMS data shows that H atoms are distributed well beyond the ion projected range. Isochronal annealing appears to suggest two H release stages that might be associated with the reported activation energies. H release at RT was observed between days 10 and 70 following ion implantation, and the level was maintained over the next 60 days. In addition, FIB/SEM results exhibit H2 blister formation near the surface of the as-implanted W. The blister distribution remains unchanged after thermal annealing up to 600 ˚C.